Changes in erythropoietin and vascular endothelial growth factor following the use of different altitude training concepts - Wisniewska, A.; Ploszczyca, K.; Czuba, M. (The Journal of Sports Medicine and Physical Fitness, 2020)
BACKGROUND: Erythropoietin (EPO) and vascular endothelial growth factor (VEGF) are important factors regulating erythropoiesis and angiogenesis. Altitude/hypoxic training may induce elevated VEGF-A and EPO levels. However, it appears that the range of adaptive changes depends largely on the training method used. Therefore, we investigated the changes in EPO and VEGF-A levels in athletes using three different altitude/hypoxic training concepts. METHODS: Thirty-four male cyclists were randomly divided into four groups: LH-TL group ("live high-train low" protocol), HiHiLo ("live high - base train high - interval train low" procedure), IHT ("intermittent hypoxic training") and control group (CN, normoxic training). The same 4-week training program was used in all groups. Blood samples were taken before and after each training week in order to evaluate serum EPO and VEGF-A levels. RESULTS: In the LH-TL and HiHiLo groups, EPO increased (P<0.001) after 1st week and remained elevated until 3rd week of altitude training. In the IHT and CN groups, EPO did not change significantly. VEGF-A was higher (P<0.001) after 2nd and 3rd week of training in the IHT group. In the HiHiLo group, VEGF-A changed (P<0.05) only after 3rd week. No significant changes of VEGF-A were noted in the LH-TL and CN groups. CONCLUSIONS: Altitude/hypoxic training is effective in increasing VEGF-A and EPO levels. However, a training method plays a key role in the pattern of adaptations. EPO level increase only when an adequate hypoxic dose is provided, whereas VEGF-A increases when the hypoxic exposure is combined with exercise, particularly at high intensity.